Height, Health and History: Nutritional Status in the United Kingdom, 1750-1980 - Eltis, David (Labour / Le Travail, 1991)
The article reviews the book, "Height, Health and History: Nutritional Status in the United Kingdom, 1750-1980," by Roderick Floud, Kenneth Wachter & Annabel Gregory.
Keywords: BOOKS – Reviews; FLOUD; Roderick; GREGORY; Annabel; HEIGHT; Health & History: Nutritional Status in the United Kingdom; 1750-1980 (Book); Nonfiction; Nutrition; WACHTER; Kenneth